Atividades experimentais: implicações no ensino de biologia - Morais, Vânia Cardoso da Silva (2015)
Through quantitative and qualitative descriptive research, we intended to study experimental activities in teaching Biology for the purpose of determining if simple experimental activities can affect student motivation in Biology classes. Furthermore, we intended to examine the possibilities and difficulties in developing such activities in Biology classes in the public school, and create an educational product that assists teachers in their teaching practice and then place it on the site of the Graduate Studies Program in the Teaching of Math and Sciences of the Universidade Federal de Uberlândia, Uberlandia, MG, Brazil. This study was developed with students in the three years of High School of the Escola Estadual Arlindo Porto (Arlindo Porto State School), Chumbo district, in the city of Patos de Minas, MG, Brazil. Data were collected through application of initial and final individual questionnaires, through writing up reports, and through filming and taking pictures of some Biology classes. The themes of the practical and experimental classes were chosen in accordance with theory, based on the Common Basic Curriculum (CBC) of Biology of the State of Minas Gerais, Brazil. All the experimental activities were carried out in the classroom, schoolyard, or area just outside the classrooms since the school does not have a Science Laboratory. To develop the activities, guides were prepared in which the students analyzed the results and answered some questions about the concepts dealt with, so as to analyze the spontaneous concepts of the students. The result of the study indicated that there is greater motivation of the students with the experimental activities. It also indicated that such activities, if used within a well-based teaching practice based on the Dynamics of Three Pedagogical moments and cultural-historical perspective is a pedagogical tool linked to theory, can improve student learning.